Evaluation of radiological changes of symphysis pubis in patients with psoriatic arthritis (Annals of Medical Research, 2023)
Aim: Psoriatic arthritis (PsA) is a member of the spondyloarthropathy (SpA) group of diseases; it can lead to joint damage by causing bone erosions and/or new bone formation in the axial or peripheral musculoskeletal system. Symphysis pubis is an important joint area that can be frequently involved in rheumatologic diseases. Pubic radiological changes have been evaluated in some rheumatologic disease except PsA. In our study, we aimed to investigate the symphysis pubis joint changes in PsA and wanted to draw attention to pubic joint involvement, which is often overlooked and causes hip and inguinal pain.Materials and Methods: Pelvic and sacroiliac joint radiographs of 61 PsA patients were retrospectively analyzed. All patients were older than 18 years of age, met the criteria for the Classification Criteria for Psoriatic Artritis (CASPAR), had no history of pubic trauma, had a disease duration of at least 5 years.  Articular involvement patterns of the patients (asymmetric oligoarticular, symmetrical polyarticular, distal interphalangeal joint and axial involvement), dactylitis, scalp and nail involvement were also examined, and the relationship of these clinical conditions with changes in the symphysis pubis was investigated.Results: In the study, the data of 61 patients, 41 (67.2%) female and 20 (32.8%) male, diagnosed with PsA according to the CASPAR criteria were evaluated. There was pubic involvement in 15 (26.2%) patients. Sacroiliac involvement, scalp involvement of psoriasis and presence of dactylitis were found to be higher in patients with pubic involvement. Axially involved PsA (60%) was the most common in those with pubic involvement.Conclusion: We showed that there are pubic changes in patients and that pubic involvement is more common in the presence of scalp involvement and dactylitis.